THE EFFECT OF WATERPROOF COSMETICS ON THE LEGITIMACY OF WUDHU (Study on Islamic Boarding School Students University of Muhammadiyah Surakarta) - Mustika Utin RochmawatiI; Amrin Amrin; Ishma Amelia (Profetika: Jurnal Studi Islam, 2022)
This study aims to determine How Waterproof Cosmetics Affect the Validity of Wudhu. This type of research uses a qualitative type with field studies in the Islamic Boarding School for Students of the Muhammadiyah University of Surakarta. While the research approach used isPhenomenologicalwith the analysis of the data used is using inductive analysis. The results of this study indicate that first, the use of waterproof cosmetics by students is very high, and significantly it affects the use of waterproof cosmetics. Second, the use of waterproof cosmetics gives the invalid status of the legal requirements for ablution due to the presence of substances that block the neutralization of water entering the skin pores which is a condition for valid ablution.